Comprehensive Database for Nutrient Composition of Major Food Items and Underutilized Plant Species in Africa - Gbahoungbola, Hessede Modoukpe; Odongo, Nicanor; Bodjrenou, Sam; Donkor, Emmanuel; Ndindeng, Sali; Parvez, Haris; Brima, Eid; Frei, Michael; Justus Liebig University Giessen (My University, 2025)
The current version of the database contains 196 foods - 51 vegetables, 79 fruits, 47 seeds and nuts, 19 roots and tubers. It focuses on major foods and underutilized plant species, including vegetables, fruits, seed, nuts and roots and tubers. The aim of the database is to gain a comprehensive understanding of the nutritional content of major foods and underutilized crops consumed in eight African countries. This will enable us to promote their production and consumption, contributing to improved food and nutritional security. The database was created using Microsoft Excel and is 3.91 MB.
Keywords: Food security; Underutilized plant species; Nutrient composition; Major food items; Food system diversification; Africa; ddc:630